Sport Tourism Profile in Sumedang Regency - Bahtiar, Agung; Indra Safari; Rizal Ahmad Fauzi (Universitas Negeri Semarang, 2024)
The purpose of this research is to describe sport tourism places in Sumedang Regency and to find out how much sport tourism there is in Sumedang Regency. Based on this, researchers want to collect data to be used as recommendation material for the Tourism, Culture, Youth and Sports Office (Disparbudpora) and become information material for visitors. So that it can provide excellent opportunities for the local community in the economic field. The research method used is a qualitative method with a descriptive research design in the form of interviews, observation and documentation. Sumedang Regency is a hilly and mountainous area with altitudes between 25 m - 1,667 m above sea level. Most of Sumedang is mountainous, except in a small part of the northern region which is lowland. Mount Tampomas (1,667 m), is located in the north of Sumedang Urban Area. Sumedang Regency as a tourism area is very potential, especially after the construction of the Cileunyi - Sumedang - Dawuan (Cisumdawu) Freeway which connects Bandung with Cirebon through the Cipali Trans Java Toll Road. The easier accessibility to Sumedang will contribute to the flow of tourists entering the Sumedang area. Based on the results of interviews with the Department of Tourism, Culture, Youth and Sports (Disparbudpora), the agency has not coordinated and collected data on the number of sport tourism in Sumedang Regency. It was concluded that Sumedang Regency has eight sports tours namely: Paragliding, Rafting, Horse Racing, Mountain Bike, Motocross, Offroad, Golf and Pencak Silat Village. The eight sports tours are further divided into three according to the place, namely water, land and air sports tours.